2017
DOI: 10.13109/diac.2017.8.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Men and women in partnership: Mobilizing faith communities to address gender-based violence

Abstract: There is much debate around whether gender-based violence (GBV) interventions should be framed within 'women' or 'men' movements. While recognizing the gains made through both strategies, by drawing on data collected during a recent scoping study on the role of faith communities and organizations in the prevention and response to sexual and genderbased violence, we argue that there is a need, particularly within faith communities in the Global South, to explore the notion of an integrated approach. The dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Religiosity can legitimize and predict acceptance of FDV through beliefs and teachings that emphasise male authority and female submission. Male perpetrators of violence against women have been found to justify their behaviour based on patriarchal religious ideologies and interpretations of sacred texts (Le Roux & Bowers-Du Toit, 2017; Lock, 2018; Ringel & Park, 2008). Women in faith communities who experience violence often use religious language and symbolism to explain and tolerate violence, and remain in abusive relationships longer than other women (Hosseini-Sedehi, 2016; Knickmeyer, Levitt, & Horne, 2010; Popescu et al, 2009; Westenberg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Religiosity can legitimize and predict acceptance of FDV through beliefs and teachings that emphasise male authority and female submission. Male perpetrators of violence against women have been found to justify their behaviour based on patriarchal religious ideologies and interpretations of sacred texts (Le Roux & Bowers-Du Toit, 2017; Lock, 2018; Ringel & Park, 2008). Women in faith communities who experience violence often use religious language and symbolism to explain and tolerate violence, and remain in abusive relationships longer than other women (Hosseini-Sedehi, 2016; Knickmeyer, Levitt, & Horne, 2010; Popescu et al, 2009; Westenberg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness-building problems should be devised in ways that decrease the risk of the perceived threat that comes from female empowerment. To minimize the perceived threat from such programs, we could co-opt a patriarchal hierarchical structure by engaging with traditional authority figures such as faith organizations (le Roux and Bowers-Du Toit 2017 ). We should also engage with men, at-risk groups for OGBV perpetration, by building supportive peer groups of gender-aware men (Greig et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has shown that deterrent convictions enabled by free legal representation in courts, community mobilization on violence against women and formation of gender dialogue groups have been helpful in combatting violence against women. Scholars have previously documented that mobilizing both men and women to fight gender based violence plays a major role in mitigating it (Le Roux& Bowers-Du Toit, 2017, Greig &Edström, 2012, Casey et al, 2018.…”
Section: Discussion Of Findingsmentioning
confidence: 99%